Provenance and fate of arsenic and other solutes in the Chaco-Pampean Plain of the Andean foreland, Argentina: From perspectives of hydrogeochemical modeling and regional tectonic setting - Raychowdhury, N.; Mukherjee, Abhijit; Bhattacharya, P.; Johannesson, K.; Bundschuh, J.; Sifuentes, G.; Nordberg, E.; Martin, R.; Storniolo, A. (Elsevier BV, 2014)
© 2013 Elsevier B.V. Extensive arsenic (As) enriched groundwater is known to occur in the aquifers of the Chaco-Pampean Plain of Argentina. Previous studies speculated that the As mobilization in these groundwaters was a direct result of their elevated pH and oxidative conditions. The volcanic glass layers present in the aquifer matrix were hypothesized as one of the possible sources of As to the groundwaters. Here, we examine the groundwater chemistry of the Santiago del Estero province of Chaco-Pampean Plains of Argentina, and test these hypotheses by using hydrogeochemical modeling within the framework of the regional geologic-tectonic setting. The study area is located in the active foreland of the Andean orogenic belt, which forms a continental arc setting, and is dotted with several hot springs. Rhyolitic volcanic glass fra gments derived from arc volcanism are abundant within the aeolian-fluvial aquifer sediments, and are related to the paleo-igneous extrusion in the vicinity. Hydrogeochemical analyses show that the groundwater is in predominantly oxidative condition. In addition, some of the groundwaters exhibit very high Na, Cl - and SO42- concentrations. It is hypothesized in this study that the groundwater chemistry has largely evolved by dissolution of rhyolitic volcanic glass fragments contained within the aquifer sediments along with mixing with saline surface waters from, adjoining salinas, which are thought to be partially evaporated remnants of a paleo inland sea. Flow path modeling, stability diagrams, and thermodynamic analyses undertaken in this study indicate that the dominant evolutionary processes include ion exchange reactions, chemical weathering of silicate and evaporites, in monosialitization-dominated weathering. Geochemical modeling predicts that plagioclase feldspar and volcanic glass are the major solids phases that contribute metal cations and dissolved silica to the local groundwaters. Co-influxed oxyanions, with similar ionic radii and structure (e.g. Mo, Si, V, PO43-), compete with As for mineral surface site, leading to As mobilization to the groundwaters (without considering the influence of microbial activities). Further, the transition of the Ca-rich groundwater to Na-rich groundwater, by mixing with water from the salinas and/or evaporative concentration, might also have led to counter-ion effects (a type of ion exchange reactions), and hence, further enrichment of groundwater by As. Some of the As may also have been contributed from mixing of meteoric water with magmatic-sourced water in the geothermal springs.